Terrestrial isopod (Crustacea, Isopoda) assemblages near a local road in a forested region from Oaș Mountains, North-Western Romania - FERENȚI, Sára; VINTER, Mariana Lucia; MOȘ, Andreea-Selena; CICORT, Abigail; COVACIU-MARCOV, Severus-Daniel (Studia Universitatis Babeș-Bolyai Biologia, 2024)
Roads are in permanent expansion at the global level and have numerous negative effects, impacting even the litter-dwelling invertebrates from their vicinity. In this context, we studied the terrestrial isopod assemblages from the vicinity of a local road situated in a forested region in Oaș Mountains (North-Western Romania) with the direct collecting method, where we encountered 17 terrestrial isopod species. Most of them were native species related to forested and wet areas. We also recorded species that are endemic to the Carpathian Mountains and species that are rare in the country. Thus, we recorded Trichoniscus provisorius, mentioning it for the second time in the country, both distribution records being situated in North-Western Romania. The terrestrial isopod assemblages from the road edges were diverse, as the species number resembles the number previously registered in the natural areas of North-Western Romania. The synanthropic and generalist species and individuals were only a few, recorded especially in the vicinity of the Negrești-Oaș town. Because this local road is situated in the middle of a region covered with vast and natural forests, it did not succeed in modifying the isopod assemblages, which, even on the road edges, resemble the assemblages from the region's natural habitats. Article history: Received 19 October 2024; Revised 02 December 2024; Accepted 04 December 2024; Available online 15 December 2024